Single crystal synthesis, structure, and magnetism of Pb10−xCux(PO4)6O - P. Puphal; M. Y. P. Akbar; M. Hepting; E. Goering; M. Isobe; A. A. Nugroho; B. Keimer (APL Materials, 2023)
The recent claim of superconductivity above room temperature in Pb10−xCux(PO4)6O with 0.9 < x < 1 (referred to as LK-99) has sparked considerable interest. To minimize the influence of structural defects and impurity phases on the physical properties, we have synthesized phase-pure single crystals with a copper doping level of x ∼ 1. We find that the crystals are highly insulating and optically transparent. X-ray analysis reveals an uneven distribution of the substituted Cu throughout the sample. Temperature (T) dependent magnetic susceptibility measurements for 2 ≤ T ≤ 800 K reveal the diamagnetic response characteristic of a non-magnetic insulator, as well as a small ferromagnetic component, possibly originating from frustrated exchange interactions in Cu-rich clusters in the Pb10−xCux(PO4)6O structure. No anomalies indicative of phase transitions are observed. We, therefore, rule out the presence of superconductivity in Pb9Cu(PO4)6O crystals and provide some considerations on the origin of anomalies previously reported in experiments on polycrystalline specimens.